FREELANCING IN THE DIGITAL AGE: UNDERSTANDING FIVERR WITHIN THE GIG ECONOMY - Lutz, Christoph; Whalley, Jason; Stocker, Volker (AoIR Selected Papers of Internet Research, 2025)
Platforms play an increasingly prominent role in today’s economy. As big tech companies like Alphabet, Meta and Alibaba leverage their size and access to large amounts of data to provide value for their users and shareholders, platforms have begun to emerge within the gig economy. The gig economy is where individuals rent out their labour, and has rapidly grown in recent years. This paper focuses on Fiverr, an online freelancing platform in the gig economy that allows individuals to sell their services to anyone who can access it. We undertake a longitudinal case study, exploring and analysing how Fiverr has developed its business to provide a number of services that facilitate the operation of the platform. We explain growth drivers, innovation strategies and show how they favour the buyer, which has created tensions in the operation of the platform. Additionally, we contextualize Fiverr, and online freelancing more generally, within two major socio-technical developments in recent years, namely the Covid-19 pandemic and the rise of generative AI, showing the turbulent times such platforms are currently facing.